Kandungan klorofil dan lipid Nannochloropsis oculata yang dikultur dalam media limbah cair karet - Tri Rima Setyawati, Sartika, Mukarlina (Jurnal Protobiont, 2014)
The chlorophyll and lipid content in N. oculata can be influenced by the concentration of the culture medium. One of the substances, which has the potential to be an alternative culture medium, is rubber liquid waste. The purpose of this research was to understand the rubber liquid waste influence and its level of concentration as the alternative culture medium for N. oculata in terms of the chlorophyll and lipid content. The research was an experimental study with completely random design with six treatments are the control (sea water), the concentration 10%,20%,30%,40% and 50% of rubber waste liquid. The chlorophyll content was measured by using spectrophotometer method, while the lipid content was measured by using Bligh and Dyer method. The ANOVA results of chlorophyll a and lipid content were showed a significant effect on the content of N. oculata chlophyll (F5,12 = 9,194; p < 0,05) and lipid (F5,12 = 23,818; p < 0,05). The result of the experiment demonstrated that the highest amount of chlorophyll and lipid was produced by the 10% concentration, 37.71 µg/ml and 3.77 g/200 ml respectively. Furthermore, the 50% concentration produced the lowest amount of chlorophyll and lipid, 2.37 µg/ml and 0.82 g/200 ml respectively.